A proposta curricular do curso de pedagogia da UERR e a realidade multicultural de Roraima - Oliveira, Elialdo Rodrigues de (2016)
The study field concerning the curriculum, in the sphere of the Basic Education or of the Higher Education, it has gained a space more and more accentuated at the present time in the social, political and economical debates. The curriculum, thankfully as conflict space, when being taken as function of an education capable to answer to the longings and needs of a formative process, in the understanding and significance of the interaction among you produced knowledge scientifically and the knowledge about the lived experience, it became a representative determinant in the teachers' formation to act in contexts marked by the cultural diversity that is expressed in the representation of identities in local and global levels. The multicultural phenomenon, expressively more and more intensified in the age of the globalization, it pleads an curricular organization for the ruled educational formation in the dialogue, respect, reflexive autonomy, tolerance and understanding of the "world of the life" as construction possibility and production of a more human knowledge and humanized in the school space. The present study has as guiding problem to know as the curriculum of the Course of Pedagogy of UERR occurs and it accomplishes in relation to the reality multicultural of Roraima in the teachers' formation, identifying your principal limitations and possibilities. The research that based this work understands Roraima as specific context, starting from the significances and extracted world representations of the experiences lived by teachers and managers that act in the educators' formation, through the State University of Roraima (UERR). Starting from inductive and deductive principles, it took as methodology the modality of phenomenological research, with a variation of methods demanded to that investigation type in the qualitative research. It was used the free observation and the interview technique semi-structured in the search of mechanisms and resources based in the expressed world representation in the teachers' significances and managers of the Course of Pedagogy. The interpretative analysis occurred by means of indentation and categorization of significances in ideographic and nomothetic matrices. It points the process of inherent significances to the study, referring to the discussion proposed in the presented text, detaching the need of a perception curricular of the course on the context local multicultural, with an appropriate formation of the teacher‟s trainer for the execution curricular of the course, as well as the need of better academic infrastructure of the University and a proposed curricular that he/she is born of the local reality for that reality in an integral way that it promotes the interaction and epistemological integration epistemological and cultural of the curricular matrix of the course, starting from the significance and theoretical and practical resignification of diversified curriculum